Nearly Three Centuries of Lava Flow Subsidence at Timanfaya, Lanzarote. (19th October 2022) - Purcell, Victoria; Reddin, Eoin; Ebmeier, Susanna; González, Pablo J.; Watson, Andrew; Morishita, Yu; Elliott, John
Abstract: The 1730–1736 eruption on Lanzarote was one of the most significant volcanic eruptions to occur on the Canary Islands, with lavas covering over 200 km 2 . Globally, it is volumetrically the third largest known subaerial basaltic fissure eruption in the past 1, 100 years. Here we use Sentinel‐1 and ENVISAT interferograms on both ascending and descending orbits to construct a time series of line‐of‐sight surface displacements and calculate linear vertical deformation rates. We resolve a constant subsidence rate of about 6 mm/yr associated with an area of ∼20 km 2 within the central and western portion of the Timanfaya lava flows relative to the rest of the island. This is consistent over the 28‐year period (1992–2020) covered by the Sentinel‐1 and ENVISAT data when combined with the previously published European Remote‐Sensing Satellite data. Time series constructed using Sentinel‐1 short interval interferograms have previously been shown to suffer systematic biases and we find that by making longer period interferograms these biases can be mitigated (when compared against an averaged stack of 1‐year interferograms). Cooling‐driven contraction of an intrusion would require improbably large sill thickness to achieve the observed subsidence rates. Our observations are consistent with the cooling of lavas on the order of one hundred meters, twice as thick as previous estimates, which suggests overall lava volume for this eruption may have been underestimated. This is also evidence of the longest duration of lava flow subsidence ever imaged which indicates that these cumulative thick flows can continue to deform significantly even three centuries after emplacement. Plain Language Summary: A common result of a sustained volcanic eruption is large outpourings of lavas that can form thick flows when activity lasts many years. One of the ways to measure the behavior of active volcanoes is to use satellites to observe how fast parts of the volcano surface are moving. It is important to be able to estimate the different physical processes that may lead to the surface deformation around a volcano. One of these processes is the contraction of thick lava flows which rapidly subside due to cooling. Here we use radar satellites to measure how fast parts of Lanzarote are sinking. We find that despite these lava flows being nearly three centuries old, they are still sinking at about half a centimeter every year. These are the oldest flows known to still be measurably subsiding. This shows that when multiple stacked lava flows get very thick (here estimated at over 100 m in thickness), they are still able to continue deforming centuries later. It is important to know this is due to lava subsidence as other magmatic processes can also lead to subsidence and these might be of greater hazard concern and could indicate the subsurface migration of magma. Key Points: We detect multi‐decade subsidence of up to 6 mm/yr across Timanfaya lavas emplaced almost 300 years ago using Interferometric Synthetic Aperture Radar time series Peak subsidence is consistent with the cooling of 100–150 m thick lava flows We demonstrate mitigation of time series bias from short‐period interferograms in Sentinel‐1 by using longer networks